2013
DOI: 10.1210/jc.2012-2666
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of miR-146b Expression and Its Functional Role in Papillary Thyroid Carcinoma

Abstract: Context: Recent studies suggest that miR-146b deregulation in papillary thyroid carcinoma (PTC) was associated with advanced tumor characteristics. However, the influence of miR-146b expression on the prognosis of PTC remains unknown. We sought to correlate tumor expression levels of miR-146b with the prognosis of a previously reported PTC cohort and reveal the underlying mechanisms via a PTC cell line model. Methodology:Expression levels of miR-146b were assessed via quantitative real-time PCR in 71 cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
146
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(158 citation statements)
references
References 34 publications
11
146
0
1
Order By: Relevance
“…Elucidation of sensitive biomarkers allowing for identification of such patients would significantly facilitate the treatment and monitoring of their health status. In PTC, miR-146b promotes cell migration and invasion and is associated with an increased risk of recurrence (50). Recently, it has been shown that PTC cases with overexpression of miR-146b-5p and miR-21 had significantly poorer disease-free survival rates.…”
Section: Micrornas In Cancer Prognosticsmentioning
confidence: 99%
“…Elucidation of sensitive biomarkers allowing for identification of such patients would significantly facilitate the treatment and monitoring of their health status. In PTC, miR-146b promotes cell migration and invasion and is associated with an increased risk of recurrence (50). Recently, it has been shown that PTC cases with overexpression of miR-146b-5p and miR-21 had significantly poorer disease-free survival rates.…”
Section: Micrornas In Cancer Prognosticsmentioning
confidence: 99%
“…The candidate targets of these miRNAs could be p27kip1, a cell cycle progression inhibitor, and KIT, a receptor tyrosine kinase that plays important roles in cell growth and differentiation [143,148]. Interestingly, high expression levels of miR-146b were found to be correlated with lower overall survival and with the development of drug resistance [149]. A recent study demonstrated that miR-146b could cause thyroid cancer development by regulating TGF-␤ signaling, although the mechanisms of miR-146b-mediated tumor behavior in PTC are largely unknown [150].…”
Section: Micrornasmentioning
confidence: 99%
“…There are several studies reporting overexpression of miRNAs including miR-222, miR-221, and miR-146b in PTC and these miRNAs may be of diagnostic potential [143][144][145][146][147][148][149][150][151]. In a recent study, a panel of seven miRNAs was used in thyroid FNAB samples [223].…”
Section: Molecular Targets In Histopathological Diagnosis and Classifmentioning
confidence: 99%
“…Different miRNA expression profiles have been observed in ATC, with elevated expressions of miR-17, miR-221, miR-222 and decreased let-7, miR-30 and miR-29 expressions as compared to normal thyroid tissue (Mancikova et al 2015). Moreover, the differential expression of some of these and other miRNAs is associated with TC aggressiveness, epithelial-mesenchymal transition, vascular invasion, lymph node dissemination, risk of recurrence and dedifferentiation, including increased expression of miR-9, miR-21 and miR-146b, HMGB1-induced miR-221 and miR-222 upregulation and miR-204 downregulation (Braun et al 2010, Mardente et al 2012, Chou et al 2013, Cancer Genome Atlas Research Network 2014, Guo et al 2015, Sondermann et al 2015. By specifically downregulating hNIS expression, miR-339 and miR-146b are identified to promote TC dedifferentiation and RAI resistance (Lakshmanan et al 2015, Riesco-Eizaguirre et al 2015.…”
Section: Transcriptional Regulation By Mirnasmentioning
confidence: 99%